Knoevenaqgel Condensation of Trans-3-(2-furyl ) Acroline with Heterocyclic Active Methylene Compounds - Abdo, Abdel- Wahab (Iraqi Journal of Science, 2023)
A new route of knoevenagel condensation for trans-3-(2-furyl)acroline with Rhodanine, Barbituric acid ,Thiazolidine-2,4-dione and 2-Thiohydantoin,in the presence of cetyltrimethylammoniumbromide(CTMAB) at room temperature in water .